Characterization of mechanical properties on natural fibre reinforced polymer using kenaf and polyurethane - Isa M.R.; Suhaimi A.B.; Zaroog O.S.; Zahari N.M.; Sulaiman S.N.; Ismail I.N.; Mohamed H. (American Institute of Physics Inc., 2023)
Natural fibre composition is one of the excellent alternative for the most extensively utilized fibre in the composite revolution such as covers; vehicle door's panel and automobile roofs. Renewable, low cost and also decomposable (biodegradable) are some of benefits natural fibre composites. In latest years, a lot of researchers involved in natural fibre project to reinforced polymer. This study was done using kenaf fibres and polyurethane (PU) as the polymer. Composites have been organized the usage of the three unique percentages of composites 2%, 4% and 6% of kenaf fibre. The hardened composites were cured for 24 hours earlier than it was once shaped in accordance to precise dimensions. Mechanical tests were performed on the samples to study the behavior. In addition, the morphology of the materials were observed using scanning electron microscope (SEM) Result found that the 6% of kenaf fibre has the highest hardness value, tensile as well as impact strength. It could be seen using SEM that 6% fiber loading showed lesser void and superior interfacial bonding between the fiber and polymer matrix. 2019 Author(s).